2013
DOI: 10.1021/jp3121319
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriopheophytin a in the Active Branch of the Reaction Center of Rhodobacter sphaeroides Is Not Disturbed by the Protein Matrix as Shown by 13C Photo-CIDNP MAS NMR

Abstract: The electronic structure of bacteriopheophytin a (BPhe a), the primary electron acceptor (ΦA) in photosynthetic reaction centers (RCs) of the purple bacterium Rhodobacter sphaeroides, is investigated by photochemically induced dynamic nuclear polarization (photo-CIDNP) magic-angle spinning (MAS) NMR spectroscopy at atomic resolution. By using various isotope labeling systems, introduced by adding different (13)C selectively labeled δ-aminolevulinic acid precursors in the growing medium of R. sphaeroides wild t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 61 publications
5
15
0
Order By: Relevance
“…The lineshape is more than 90% Lorentzian. That is in-line with previous experiments (35,81) concluding that the narrow line width is a strong argument for a structurally stiff and well structured cofactor arrangement along the electron transfer chain.…”
Section: Assignment Of Signals In the 2d Photo-cidnp Inadequate Mas Nsupporting
confidence: 92%
See 3 more Smart Citations
“…The lineshape is more than 90% Lorentzian. That is in-line with previous experiments (35,81) concluding that the narrow line width is a strong argument for a structurally stiff and well structured cofactor arrangement along the electron transfer chain.…”
Section: Assignment Of Signals In the 2d Photo-cidnp Inadequate Mas Nsupporting
confidence: 92%
“…Analysis of the RCs of R. sphaeroides, employing photo-CIDNP MAS NMR, has demonstrated that the origin of the functional symmetry break is not due to the acceptor (35) but that the electronic structure is already broken in the "dark" ground-state electronic structure (36)(37)(38). Also in the radical-pair state, the electron spin density is asymmetrically distributed over the Special Pair (38), an observation well in-line with previous 1 H-ENDOR studies (39).…”
Section: Introductionsupporting
confidence: 84%
See 2 more Smart Citations
“…showing the same features as observed in spectra of an u-13 C-ALA labeled sample under continuous illumination 21 . The slightly dispersive difference shape of the carbonyl signal probably originates from potential phase shifts by heating.…”
Section: Resultssupporting
confidence: 76%